1966
DOI: 10.1021/je60030a010
|View full text |Cite
|
Sign up to set email alerts
|

Densities of Binary and Ternary Aqueous Solutions of NaCl, Na2SO4 and MgSO4 of Sea Waters, and Sea Water Concentrates.

Abstract: Densities of binary and ternary aqueous solutions of NaCI. NazSOd, and MgSOl have been determined from 25' to 175'. The solutions contained these compounds at concentrations corresponding to sea water and its concentrates up to fivefold concentration. A simple method of determining the densities of binary and ternary solutions is bared on apparent molal volumes of these compounds over a wide temperature range. Literature data on densities of sea water and its concentrates have been critically correlated. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0

Year Published

1975
1975
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 6 publications
5
20
0
Order By: Relevance
“…In all, over 40 data sets are found for the density (volume) of (NaCl + H 2 O) system with a wide T, P, m range and experimental precision of 0.0001% to 0.1%. Most of the experimental data between T = (273 and 573) K are consistent with each other except for the small number of data points [48][49][50], whose density (volume) data apparently deviate from other data sets over the same T, P, m range. Therefore, all data points but those of [48][49][50] are included in the parameterization that cover a wide T, P, m range, respectively (273 K to 573 K, 0.1 MPa to 100 MPa, and 0 to 6 molal) for the (NaCl + H 2 O) system.…”
Section: Review Of the Density Data Of Binary Aqueous Chloride Solutionssupporting
confidence: 58%
“…In all, over 40 data sets are found for the density (volume) of (NaCl + H 2 O) system with a wide T, P, m range and experimental precision of 0.0001% to 0.1%. Most of the experimental data between T = (273 and 573) K are consistent with each other except for the small number of data points [48][49][50], whose density (volume) data apparently deviate from other data sets over the same T, P, m range. Therefore, all data points but those of [48][49][50] are included in the parameterization that cover a wide T, P, m range, respectively (273 K to 573 K, 0.1 MPa to 100 MPa, and 0 to 6 molal) for the (NaCl + H 2 O) system.…”
Section: Review Of the Density Data Of Binary Aqueous Chloride Solutionssupporting
confidence: 58%
“…Nilsson [2007] reported that H-TDMA growth factors measured for seawater samples taken from the Baltic Sea (water depth, 1-2 m) and Atlantic (~3000 m) to be g (90%) = 2.1 for 100 nm dry size particles, which is in good agreement with the seawater-water activity reported by Tang et al [1997] with Electrodynamic Balance. Interestingly, the observed mean growth factor g(90%) = 1.79 at Chichijima is slightly lower than those (g(90%) > 1.85) reported for the marine aerosols from different sites [Sverdrup et al, 1942; Fabuss et al, 1966;Tang, 1997;Nilsson, 2007;Swietlicki et al, 2008].…”
Section: Concentrations Of Somentioning
confidence: 59%
“…[] with Electrodynamic Balance. Interestingly, the observed mean growth factor g (90%) = 1.79 at Chichijima is slightly lower than those ( g (90%) > 1.85) reported for the marine aerosols from different sites [ Sverdrup et al ., ; Fabuss et al ., ; Tang , ; Nilsson , ; Swietlicki et al ., ].…”
Section: Resultsmentioning
confidence: 99%
“…k HO 12 ¼ C 22 (55) in which ε HO 12 is the well depth of the siteesite interaction potential energy between a site of type H in component 1 and a site of type O in component 2, and k HO 12 is a measure of the volume available for bonding between a site of type H in component 1 and a site of type O in component 2.…”
Section: H 2 S(1)eco 2 (2)e Brine (H 2 O(3)enacl(4))mentioning
confidence: 99%